Teacher's Strategy to Increase Culture and Citizenship Literacy for CLC Students in Sabah, Malaysia - Siregar, Firda; Widiastuti, Anik; Saliman, Saliman; Yaacob, Norazlan Hadi (Harmoni Sosial: Jurnal Pendidikan IPS, 2024)
This paper reviews on strategies or  approaches made by Community Learing Centers/CLC teachers to teach and internalize the knowledge about Indonesian values and cultures for Indonesian students who are born and raised overseas particulary Indonesian students in CLCs in Sabah, Malaysia. Knowledge of Indonesian values and culture will encourage students to enhance their sense of nationalism and help them to identify themselves as Indonesians.This paper aims to examine the strategies or approaches of CLC's teachers in enhancing cultural and civic literacy among their students of Indonesian nationals. This paper untilizes qualitative method through interviews and close observations of teachers of CLCs in applying their strategies to educate their students in regarding their Indonesian identity. After obtaining the data, the analysis is conducted through the interactive analysis particularly under the scope of Miles and Huberman's theories. Further examination founds that strategies employed by CLC teachers to enhance cultural and civic literacy for their students are including habituation and implementation of integrated learning with Indonesian cultural elements, oral or written, through flag ceremonies, video screenings, pictures, books, festivals, extracurricular activities, and competitions.